Characteristics of a Diesel Engine with a Ceramic Coated Piston Head - Andrzej Mruk (Communications - Scientific letters of the University of Zilina, 2006)
In this age of fuel problems, the improvement in thermal efficiency of an engine is very important. One of the ways leading to this aim consists in reducing heat losses by the application of heat-insulating coatings on the elements of the combustion chamber. The article deals with the effect of the piston head heat-insulation on a Diesel engine running indicators and presents the results of the tests.